Legitimate targets? : Social construction, international law and US bombing - Dill, Janina 1983- (Cambridge University Press, 2015)
"Based on an innovative theory of international law, Janina Dill's book investigates the effectiveness of international humanitarian law (IHL) in regulating the conduct of warfare. Through a comprehensive examination of the IHL defining a legitimate target of attack, Dill reveals a controversy among legal and military professionals about the 'logic' according to which belligerents ought to balance humanitarian and military imperatives: the logics of sufficiency or efficiency. Law prescribes the former, but increased recourse to IL in US air warfare has led to targeting in accordance with the logic of efficiency"--